Evaluation of an air–liquid interface cell culture model for studies on the inflammatory and cytotoxic responses to tobacco smoke aerosols. Issue 7 (October 2015) - Azzopardi, David; Haswell, Linsey E.; Foss-Smith, Geoff; Hewitt, Katherine; Asquith, Nathan; Corke, Sarah; Phillips, Gary
Highlights Tobacco smoke induces cytotoxicity and an inflammatory response in NCI-H292 cells. Passage number has a significant effect on the response of cells to whole smoke. Vapour phase contributes approximately 90% of the cytotoxic effect of whole smoke. The cell culture system is able to differentiate between two smoking regimens.